The evaluation of vestibular functions in patients with pseudoexfoliation syndrome - Turgut, Burak; Alpay, Hayrettin Cengiz; Kaya, Mehmet Kaan; Oger, Muzaffer; Celiker, Ulku; Yalcin, Sinasi (Springer, 2010)
The main objective of the study is to evaluate vestibular system of the inner ear with postural tests in the patients with pseudoexfoliation syndrome (PEX). It is clinical case-control study. The study group included 34 patients with PEX and 40 controls without PEX. The patients and controls underwent complete ophthalmic and otorhinolaryngologic examinations. Vestibular functions were done by Fitzgerald and Dix-Hallpike, caloric tests, Romberg test, tandem Gait test, Quiks test in both control and study groups. Pur-tone and high-frequency audiography were also performed in all cases. The mean patient age was 63 years (+/- 11.80) (range 47-74 years) in the PEX group and 65 years (+/- 8.70) (range 61-68 years) in the control group with no differences among the two groups (P > 0.05). Although none of the 34 patients with PEX had clinical history of balance disturbance, 21 (61.76%) had significant pathologic sign in vestibular function tests (P a parts per thousand currency sign 0.05), while only 3 (7.5%) of 40 cases in the control group had pathologic sign in vestibular function tests. The scales from pure tone and high-frequency audiogram in the PEX group were similar to those of the control group. In conclusion, the patients with PEX, there may be a vestibular involvement in the pathological level in the inner ear. Larger clinical studies, experimental animal studies, and post mortem studies in humans are needed to disclose the pathology in the vestibulocochlear system in the patients with PEX.
Keywords: Pseudoexfoliation; Vestibular functions; Inner ear